Concepções de professores sobre gestão escolar - Jorge, Marcos [UNESP]; Telles, Tiago Santos (My University, 2012)
This study examined the newly graduated in pedagogy teachers' perceptions of current school administration concepts and practices. It is an exploratory research study with questionnaire using Likert scale closed-ended questions. The results indicate an emphasis on the official view of the school administration and the sharing of responsibilities as a democratic basis. It is concluded that the respondents have basic perceptions, little criticism on the school administration, reproducing, often a government and media discourse on the subject.

O objetivo do estudo foi identificar a percepção de professores, recém-formados em Pedagogia, sobre conceitos e práticas da gestão escolar atual. Trata-se de uma pesquisa exploratória com aplicação de questionários, com perguntas fechadas, construídas com base na Escala de Likert. Os resultados indicam ênfase na concepção oficial da gestão escolar e no compartilhamento das responsabilidades como bases democráticas. Conclui-se que os participantes da pesquisa possuem percepções básicas, pouco críticas, sobre a gestão escolar, reproduzindo, muitas vezes, um discurso midiático e governamental sobre o tema.
Teachers' conceptions about school administration
Keywords: School administration; Pedagogy; Likert scale; Educational policy; Gestão escolar; Pedagogia; Escala de Likert; Política educacional